Impact Pandemi COVID-19 terhadap Perkembangan Anak Usia Sekolah - Padila Padila; Juli Andri; Sunarsih Sunarsih; Muhammad Bagus Andrianto; Andry Sartika (Jurnal Keperawatan Silampari, 2022)
This study aims to analyze how the impact of the COVID-19 pandemic situation on the development of elementary school-age children at SD Negeri 26 Pagar Alam City. The research design used is a qualitative research with a descriptive phenomenological approach, 15 informants were taken by Stratified Random Sampling based on inclusion criteria. The instrument used is an in-depth interview guide related to the aspects studied. The results of the study obtained 3 themes, 1) Aspects of Cognitive/Language Development of Children, 2) Aspects of Children's Motor Development, 3) Aspects of Children's Socio-Emotional Development. In conclusion, the impact of the COVID-19 Pandemic on Child Development has a bad impact because online learning creates a lack of stimulation that can improve children's language, motor and socio-emotional development. Keywords: COVID-19, Impact, Development